THE INFLUENCE OF BORROWED WORDS TO THE VOCABULARY STOCK OF THE UZBEK LANGUAGE - Khamzaev, Sobir (Журнал иностранных языков и лингвистики, 2021)
The article deals with the problem of over use of foreign words in the Uzbek language. Some examples of the most obvious borrowings that violate the understanding of communication are presented in the article. Some ways of improving the literacy of borrowed words usage are also suggested in the article.